Predictors of local recurrence of renal cell cancer. Our experience - M. Y. Gaas; A. D. Kaprin; N. V. Vorobyev; A. S. Kalpinsky; V. V. Kozlov; R. O. Inozemtsev (Сибирский онкологический журнал, 2022)
Risk factors for renal cell cancer (RCC) recurrence, including its local form, include stage and high Fuhrman grading system score, regional lymph node involvement, microvascular invasion, tumor necrosis, positive surgical margin, and sarcomatoid or rhabdoid tumor differentiation. Objective. The study analyzes data from Moscow Research Oncological Institute named by PA Herzen to determine the predictors of local recurrence of kidney cancer based on the data from surgically treated patients with local recurrent RCC. Material and methods. We analyzed retrospectively data from 87 patients who were divided into 2 groups: 1-st, patients with detected local recurrence of kidney cancer (n=43), and 2-nd, control group (n=44). The following predictors were evaluated: tumor size, tumor histotype, tumor stage, Fuhrman grading system, surgical margin status, tumor necrosis, sarcomatoid and rhabdoid changes, microvascular invasion, hemorrhage and invasion of collecting system components (CSS), renal capsule, and perirenal cellular tissue and primary treatment. Results. The risk of local recurrence was higher in the primary tumor, over 40 mm in diameter (OR=5.8, p<0.001), as well as microvascular invasion and focal hemorrhage (OR=15.1, p=0.001 and OR=3.3, p=0.008, respectively). Both univariate and multivariate analyses showed a negative effect on the risk of local RCC recurrence only for tumor necrosis (OR=15.4, p<0.001 and OR=53.6, p=0.002, respectively) and high Fuhrman grade (OR=10.9, p=0.042 and OR=5.7, p=0.032, respectively). The most significant predictors of local renal cancer recurrence are tumor necrosis (p<0.001), microvascular invasion (p=0.019), positive surgical margin (p=0.009), and high Fuhrman grade (p=0.04). High Fuhrman grade (3–4) of malignancy (HR=1.9, p=0.042), tumor diameter (HR=1.0, p=0.054), positive surgical margin (HR=3.5, p=0.001), and tumor necrosis (HR=2.3, p=0.029) were found to be the most significant factors influencing 5-year local recurrence-free survival rate. Conclusion. The course of renal cell cancer is determined by multiple interrelated and independent prognostic factors.